2007
DOI: 10.1016/s1472-6483(10)61057-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age, morphology, development and chromosome abnormalities in over 6000 cleavage-stage embryos

Abstract: Previous studies assessing the relationship between embryo development, maternal age and chromosome abnormalities were either small or analysed mostly embryos not suitable for replacement. The present study includes >6000 embryos, including many suitable for replacement. Embryos with the best morphology and development were 44% euploid in patients younger than 35, decreasing to 21% in patients 41 and older. The worst morphology group had only 30% normal embryos from patients younger than 35, and 12% in embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
144
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(162 citation statements)
references
References 31 publications
6
144
0
11
Order By: Relevance
“…126 Aside from morphological evaluation, PGS using FISH or other molecular technologies such as CGH is the only tool we have for selecting the most viable embryo. 127 Independent of the fact that pregnancy rates have not improved with PGS, routine clinical application has been impaired by the complexity, invasiveness, and high cost of the procedure. Abundant research is currently being conducted in search of less invasive and more practical techniques to complement morphological assessment for embryo selection.…”
Section: Embryo Selection and Transfermentioning
confidence: 99%
“…126 Aside from morphological evaluation, PGS using FISH or other molecular technologies such as CGH is the only tool we have for selecting the most viable embryo. 127 Independent of the fact that pregnancy rates have not improved with PGS, routine clinical application has been impaired by the complexity, invasiveness, and high cost of the procedure. Abundant research is currently being conducted in search of less invasive and more practical techniques to complement morphological assessment for embryo selection.…”
Section: Embryo Selection and Transfermentioning
confidence: 99%
“…6 Aneuploidy is the most common abnormality found in embryos derived from in-vitro fertilisation (IVF), and leads to poor outcomes. [7][8][9][10][11][12][13] Morphological assessment of embryos or blastocysts alone, however, cannot negate the potential risk of replacing aneuploid embryos or blastocysts. 14 Preimplantation genetic screening (PGS) has been proposed to improve the IVF outcomes by screening for aneuploid embryos or blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Munne and coworkers (2007) reported that most morphologically normal appearing embryos (based on shape, size, blastomere number and fragmentation) may be aneuploid. In an analysis of 6000 embryos produced from oocytes of women less than 35 years of age, approximately 56% of embryos exhibiting the best morphology and development rate were actually aneuploid (Munne et al 2007). Furthermore, morphologically good, aneuploid embryos increased to nearly 80% for the women age 41 and older.…”
Section: Introductionmentioning
confidence: 99%